Time course of neuromuscular, hormonal, and perceptual responses following moderate- and high-load resistance priming exercise - Harrison, P. W.; James, L. P.; Jenkins, D. G.; McGuigan, M. R.; Schuster, R. W.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The aim of this study was to map responses over 32 hours following high-load (HL) and moderate-load (ML) half-squat priming.